The Comparative Analysis of Islamic and Conventional Monetary Financial System - Zuraidah Zuraidah (Maliki Islamic Economics Journal, 2022)
This article aims to analyze the uniqueness of Islamic financial instruments compared to conventional financial instruments and to find out what distinguishes the Islamic monetary framework from the standard monetary framework. The advantages and disadvantages of Islamic and traditional monetary frameworks are also discussed in this paper. This paper uses a writing concentrate approach by collecting information from the analytical writing in question. The side effects of the review suggest that the Islamic Monetary Framework is developing rapidly, playing its part in allocating assets and working on the turn of financial events, and implementing Islamic banking. The results also show that the advantages of Islamic finance can survive despite different monetary emergencies. The progress of Indonesian Islamic Banking evidences it compared to traditional banks.